Model-model Penciptaan Suasana Religius pada SMUN Kodia Malang - Muhaimin, Muhaimin; Ali, Nur; Sutiah, Sutiah (ULUL ALBAB Jurnal Studi Islam, 2001)
This study aims to examine how educational models create religious atmosphere in schools. This research is a concrete effort to find the right pattern to realize a religious environment in an academic context. This study uses a qualitative research approach with case study design. While the subjects in this study included a number of school principals, former principals, deputy principals, teachers and students of 4th State High School of Malang. The techniques used in data collection in this study include observations to obtain data about various teaching and learning activities, and religious activities as well as the religious atmosphere in schools as well as in-depth interviews. The implementation of religious activities in the school, which was originally "top down", was then developed to "bottom up". Through this approach, it turns out that it can bring peace, peace and increase brotherhood, unity, and friendship between leaders, employees, teachers and students. Besides, the religious atmosphere in the school is running dynamically. How to create a religious atmosphere, among others, through various types of progammed religious activities, both of Islamic and non-Islamic. In addition, school leaders use a personal approach both to students and to students' families.